Travelling to the Birthplace of "the Greatest Son of Yugoslav Nations". The Construction of Kumrovec as a Political Tourism Destination - Škrbić Alempijević, Nevena (Array, 2010)
The authors analyze the politization of the place techniques, i. e. the way in which Kumrovec was constructed as a monument of the socialist thought, and especially as a major political tourism destination. They show which facilities were built as a showcase of the state of welfare and prosperity and in which way journeys to Tito's "cradle" were highlighted as an imperative in the media discourse. On the other hand, they focus on memories and impressions of those who visited Kumrovec (state delegations, foreign politicians, groups touring the politically important Yugoslav topoi, school excursions, and individuals).